An exploratory study of a simplified approach to evaluate drug solubility in milk related vehicles - Li Sean; Gabriel Justin; Martinez Marilyn; Longstaff David; Coffey Martin; Zhao Fang (De Gruyter, 2023)
Milk related materials are frequently used as a vehicle for drug product administration. Therefore, drug solubility information in milk related vehicles is desirable for prediction of how they may influence in vivo drug release and bioavailability. However, there are very limited data published on this topic. This study explored a practical method to address the key challenges associated with solubility assessment in milk, including the sample equilibration time and cleanup procedures.